APPLYING ICT AND MULTIMEDIA INTEGRATION TO ENHANCE LISTENING AND SPEAKING SKILLS IN ENGINEERING EDUCATION: AN INNOVATIVE APPROACH IN LANGUAGE LEARNING (Lex localis - Journal of Local Self-Government, 2025)
The increasing demand for engineering graduates to communicate effectively in globalized workplaces underscores the need to strengthen not only writing proficiency but also listening and speaking skills. While traditional classroom practices in technical education often prioritize content delivery over communicative competence, the integration of Information and Communication Technology (ICT) and multimedia tools offers new opportunities to bridge this gap. This study investigates the application of ICT-enabled platforms—such as AI-driven speech recognition software, captioned video lectures, digital storytelling, and podcasting—in developing listening comprehension and oral communication among undergraduate engineering students.Adopting a mixed-methods approach, the study engages participants in a semester-long intervention combining multimedia input (authentic audio-visual materials, role-play simulations, and podcasts) with ICT-based output activities (speech analysis applications, online presentations, and peer-reviewed recordings). Quantitative data from pre- and post-tests on listening and speaking proficiency are complemented by qualitative insights from student reflections, peer evaluations, and instructor feedback.Preliminary results reveal notable gains in pronunciation accuracy, fluency, and listening comprehension, alongside enhanced learner motivation and confidence in oral communication. The findings highlight the value of ICT and multimedia as transformative tools for extending communicative competence in engineering contexts. More importantly, they demonstrate that technology-mediated practices not only support language acquisition but also simulate authentic workplace communication scenarios, preparing students for professional interactions in multidisciplinary environments.This study contributes to the growing body of research on ICT integration in language learning by extending its application from writing to oral communication skills. It emphasizes the importance of innovative instructional strategies that blend multimedia resources with interactive, learner-centered practices to achieve comprehensive language proficiency.